BER performance study of PSK-based digital modulation schemes in multipath fading environment - Paizi @ Fauzi, Wan Fariza (2006)
Digital modulation is undoubtedly significant portion in wireless communication technology. It allows the transmission of digital data via the air on high frequency carrier waves. The worst case communication channel is usually in the urban environment where there are many obstacles. Due to the obstacles and reflectors, the transmitted signal arrivals at the receiver from various directions over a multiplicity of paths. Such a phenomenon is called multipath. The project studies and identifies the PSK-based digital modulation scheme (BPSK, QPSK or GMSK) that gives the best BER performance in a multipath fading environment using computer simulation. Essentially, ideal and worst case communication channel models were studied and simulation programs were written to simulate the channels. Each PSK-based digital modulation understudy are modeled and simulated under different channel conditions. Subsequently, a comparison study is carried out to obtain the BER performance for each PSK-based transmission scheme under 1-path and 4-path multipath fading conditions and to identify which modulation scheme gives best BER performance. The comparison study showed that BER for BPSK and QPSK are similar and they give the lowest BER under multipath fading. Nonetheless, GMSK’s BER is just slightly higher than that of BPSK and QPSK. While these three modulation schemes shows high robustness under multipath fading channel, a modulation scheme that can increase transmission rate while keeping high frequency utilization efficiency should the directions of future modulation schemes. Further study on smart and adaptive modulation should also be of interest.